Towards sustainable community management of water infrastructures: results from experimental games in coastal Bangladesh [Abstract only] - Buisson, Marie-Charlotte; Das, Arijit; Mukherji, Aditi (2013)
The government of Bangladesh invested in large scale coastal embankment projects in the 1960s and 1970s, which then played an important role in protecting coastal communities from water related disasters and increasing agricultural productivity. However, maintenance of polder infrastructure has been problematic. Since the 1990s, the government of Bangladesh requires local communities to organize themselves into water management groups and to contribute toward minor maintenance of the infrastructure. Empirical evidence shows that some communities have been able to come together and collect funds for maintenance, while majority have not been able to do so. The purpose of this paper is therefore to understand the factors that determine contribution to maintenance funds by community members. For this, a public goods game was played with community participants at several locations in Coastal Bangladesh. Our results show that economic homogeneity in the group as well ions and recommendations proportional sharing of benefits increases the level of contribution. It also shows that institutional mechanisms that allow communities to be involved at an early stage of project formulation and make monetary contributions towards project implementation are more likely to contribute toward maintenance in the long term than communities who did not undergo such institutional processes.